The effect of organizational structure, personality and work motivation on teacher organization commitments on International Islamic Education Council Foundation in Jakarta and Bekasi - Maruf Akbar; Zerry Novian; Mukhneri Mukhtar (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2019)
This research aims to analyze the influence of organizational structure, personality and work motivation on teacher organizational commitment to the International Islamic Education Council Foundation in Jakarta and Bekasi. This research uses a quantitative approach with a survey method. The sample used in this study were 84 teachers who determined simple random. The research data was obtained from questionnaires and analyzed using path analysis supported by descriptive statistical analysis. The results of this study indicate organizational structure, personality and work motivation had direct effect on organizational commitment; organizational structure and personality had direct effect on work motivation; organizational structure and personality had indirect effect on organizational commitment mediating by work motivation. Therefore, improving organizational structure, personality and work motivation can improve organizational commitment.The novelty of this research is in the form of a research model of the influence of organizational structure and personality on organizational commitment with work motivation mediation developed from previous relevant studies with research locations at the International Islamic Education Council (YIIEC) Foundation in Jakarta and Bekasi, 2019.